The Practice and Challenges of Women’s Participation in Decision Making in the National Sports Organizations of Ethiopia (Indian Journal of Public Health Research & Development, 2021)
The purpose of this study was to investigate the practice and challenges of women executive members intheir participations in decision making in the National Sport organizations of Ethiopia. In the study, 21federations,4 associations and 2 committees were included. We applied descriptive design with qualitativeand quantitative method to conduct the study and the participants,from these organizations, were executiveofficers (n=162), general secretaries (n=27), and experts (n=27). The samples from each of the populationunit were selected using universal sampling technique. For analyzing the collected data, Pearson Chisquare(sig) and descriptive statistics including computation of percentile and mean were used. The resultsreveal that women executive officers in most originations have shown low performance and low participationindecision making and policy implementation of the organizations. The major inhibiting challenges havebeen found to be incompetence (p
Keywords: Decision Making,Participation, Sport Organization, Women.